Assessment of Intramuros Restaurant Services : Basis for Food Tourism as an Attraction of a Heritage Destination - Areola, PhD HSG, Eunice Mareth Querol; Escabillas, Aisha Janinne Q (Sekolah Tinggi Manajemen IPMI, 2023)
The tourists’ desire to experience local culture and heritage makes heritage sites an important attraction in destinations. Being considered an inseparable part of cultural and heritage tourism, food is an important aspect that is beneficial for the community’s economic sustainability and the social life of tourists, visitors, and usual diners. This research aimed to determine the assessments of diners on Intramuros restaurants, on the three components of guest experience with the intent of exploring food tourism as a destination attraction to promote this heritage site. It was descriptive-exploratory research using a researcher-made questionnaire to survey the assessment of 75 diner respondents in Intramuros restaurants who were selected through a purposive sampling technique. The findings of the study suggested that the respondents were satisfied with the three components of the guest experience namely: service product, service environment, and service delivery system. The respondents’ satisfaction with restaurant services offered in the destination played a significant role in their revisit and recommendation intentions where the result related a high level of likelihood of revisit and recommendation intentions among diners. Further, it determined that the top three types of food service preferences are casual dining, fine dining, and banchetto (feast). The top recommendation among five indicators in terms of food tourism activities in Intramuros, a cultural heritage site, was to associate cultural shows with the dining experience.